PENGARUH GAYA KEPEMIMPINAN KEPALA PUSKESMAS TERHADAP KINERJA TENAGA KESEHATAN (STUDI PADA PUSKESMAS PERAWATAN WAHAI KECAMATAN SERAM UTARA KABUPATEN MALUKU TENGAH) - Nilda Wahid; Petronela Sahetapy; Julia Theresia Patty (Halu Oleo University, 2025)
This study aims to determine the influence of transformational leadership style on the performance of health workers at the Wahai Health Centre in North Seram District, Central Maluku Regency. The research method used was a quantitative approach, and the data were analysed using statistics. The population in this study consisted of 79 health workers at the Wahai Health Centre, and the sampling technique used was saturated sampling. Based on the analysis results, the transformational leadership style has a significant influence on the performance of healthcare workers at the Wahai Health Centre in Seram Utara District, Central Maluku Regency. Leaders who adopt this style are able to enhance employee motivation and performance through inspiration, empowerment, and individual attention. Transformational leadership creates a strong relationship between leaders and subordinates based on trust, admiration, loyalty, and respect. Leaders not only provide a clear vision but also inspire employees to go beyond personal interests for the sake of organisational goals.